Personal correlates of creative performance: A systematic review - Cebrián, Jorge; Ramos-Villagrasa, Pedro J. (Frontiers in Psychology, 2026)
Creative performance drives innovation, problem-solving, productivity, and competitiveness of organizations. This research comprehensively reviews existing studies on employees’ creative job performance and integrates findings on individual factors that are associated with creative behavior. Examining 82 empirical studies of creative performance, 79 personal factors grouped into eight categories has been identified: demographic factors, personality, cognitive ability, motivation, emotions, self-efficacy, other performance dimensions, and a miscellaneous category. The most relevant personal factors associated with creative performance include educational level (rw = 0.19, 95% CI [.12, .27], p < 0.001; I² = 55.66%), and moderate to strong positive associations for openness (rw = 0.46, 95% CI [0.33,0.59], p < 0.001; I² = 93.76%), intrinsic motivation (rw = 0.39, 95% CI [0.28, 0.50], p < 0.001; I² = 93.37%), creative process engagement (rw = 0.52, 95% CI [0.23, 0.80], p < 0.001; I² = 97.39%), positive affect (rw = 0.31, 95% CI [0.18, 0.43], p < 0.001; I² = 81.53%), and creative self-efficacy (rw = 0.45, 95% CI [0.34, 0.56], p < 0.001; I² = 95.30%). The findings enhance the nomological network of creative performance, offer directions for future research, and suggest improvements for human resource processes, including employee selection, training, and performance assessment.